Clinical prediction models and the multiverse of madness - Riley, RD; Pate, A; Dhiman, P; Archer, L; Martin, GP; Collins, GS (BioMed Central, 2023)
Background Each year, thousands of clinical prediction models are developed to make predictions (e.g. estimated risk) to inform individual diagnosis and prognosis in healthcare. However, most are not reliable for use in clinical practice.